Factors influencing performance of public hospitals: The case of Vietnam - Duc Cuong Pham (Management Science Letters, 2019)
This paper presents an empirical investigation to identify the effects of different factors on the performance of North western public hospitals in Vietnam. Data were collected by using questionnaire delivered to 426 participants drawing from 42 public hospitals in the Northwest provinces of Vietnam. The study used correlation regression to determine the effects of different factors on the performance of the hospitals. The study used balanced score card method to study the effects of non-financial along with financial factors on the performance of the hospitals. The results show that financial figures were the most important factors influencing on the performance of the hospitals followed by customer, mission, internal process, training and staff development. Based on the research results, some key recommendations were proposed aiming to improve the performance of the public hospitals in Vietnam.